2006
DOI: 10.1093/ps/85.5.854
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbial Ecology of Broilers Vaccinated and Challenged With Mixed Eimeria Species, and Supplemented with Essential Oil Blends

Abstract: Intestinal microbiota is an important component in the development of defense mechanisms in the gut mucosa. This project determined the dynamics of intestinal microbial communities (MC) of broilers vaccinated at first day of age with live oocysts of Eimeria species and fed diets supplemented with 2 specific essential oil (EO) blends, Crina Poultry (CP) and Crina Alternate (CA). Five treatments were analyzed: 1) unmedicated-uninfected (UU) control; 2) unmedicated-infected (UI) control; 3) vaccinated with Advent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 19 publications
4
40
0
6
Order By: Relevance
“…duodenum. Mucosal lesions indicated changes in intestinal physiology that can be linked to reduction in diversity and number of fungal populations as they were observed in bacterial populations in other studies (Hume et al, , 2011Oviedo-Rondó n et al, 2006).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…duodenum. Mucosal lesions indicated changes in intestinal physiology that can be linked to reduction in diversity and number of fungal populations as they were observed in bacterial populations in other studies (Hume et al, , 2011Oviedo-Rondó n et al, 2006).…”
Section: Discussionsupporting
confidence: 52%
“…Sample DNA assayed in the current study was collected during a related study in which we examined the impact of Eimeria infection and treatment with two commercial probiotics and two essential oil blends (EO) to minimize this impact on ileal and cecal bacterial populations (Hume et al, 2011). Mixed Eimeria infection was selected as a model to study intestinal modifications caused by a common pathogen that can cause profound changes in intestinal microbial communities (Hume et al, , 2011Oviedo-Rondó n et al, 2006). Coccidiosis is one of the most endemic enteric diseases in broiler production (Dalloul and Lillehoj, 2005).…”
mentioning
confidence: 99%
“…The use of natural products as an alternative to drugs may be the best solution to this consumer demand. Many studies have reported the in vivo efficiency of natural plant extracts in the treatment of coccidiosis [14], [15], and [16]. Garlic (Allium sativum) and turmeric (Curcuma longa) were widely used to cure and prevent diseases in human beings [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A utilização de inóculo misto busca simular condições de campo e possibilita praticidade na inoculação, podendo-se, nessa modalidade de inoculação, avaliar o escore de lesões de cada espécie, escore médio de lesões e contagem de oocistos (HUME et al, 2006;OVIEDO-RONDÓN et al, 2006a;OVIEDO-RONDÓN et al, 2006b;PARKER et al, 2007). A avaliação do escore médio de lesões demonstrou uma diferença significativa para os tratamentos com níveis de 15 ppm de SEM (T3 e T5), os quais obtiveram menores escores médios de Tabela 4.…”
Section: Tratamentounclassified